Corporate Financing and Efficiency of Indigenous Energy Firms in Nigeria: A Literature Review - Odeleye, Anthonia Taye (International Journal of Energy Economics and Policy, 2013)
This paper reviews the theoretical as well as the empirics of corporate financing as it relates to the efficiency of indigenous energy firms in Nigeria. It begins with an appraisal of the sources of corporate finance and their impacts on firms operations. The study delves into the evolution of oil in Nigeria when foreigners were the sole players due to expertise and technological relevancy. The indigenisation policy of the 1970s expanded Nigerian government’s involvement in the oil sector; in 1990, following a policy statement of the then military government, oil concessions were granted to Nigerian oil companies whose ownership was truly Nigerian and whose managing directors were Nigerian citizens. Further, key analytical issues towards efficiency of the local energy firms were considered. Keywords: Corporate financing; Efficiency; Indigenous; Trade-off theory; Pecking order theory JEL Classifications: H21; Q32; Q38